Enhancing Trauma Care: A Community Service Initiative for Focused Assessment Sonography for Trauma (FAST) Training among Junior Doctors at Dr. H. Abdul Moeloek General Hospital, Bandarlampung, Indonesia - Ramadhian, Muhammad Ricky (HM Publisher, 2024)
Focused assessment sonography for trauma (FAST) is a rapid bedside ultrasound examination crucial for the initial assessment of trauma patients. This study reports on a community service initiative aimed at improving FAST competency among young doctors at Dr. H. Abdul Moeloek General Hospital, Bandarlampung, Indonesia. A mixed-methods approach was employed. The program included: 1) A pre-training assessment of FAST knowledge and skills. 2) A structured FAST training curriculum with didactic lectures, hands-on scanning sessions, and case-based discussions. 3) A post-training assessment of FAST competency. 4) Qualitative feedback from participants to assess the program's impact. Thirty-two young doctors participated in the program. There was a significant improvement in FAST knowledge (pre-test mean: 45%; post-test mean: 82%) and scanning skills. Participants reported increased confidence in FAST utilization and its integration into their trauma assessment workflow. This community service initiative demonstrated the effectiveness of a structured FAST training program in enhancing the competency of young doctors in trauma care. Such programs have the potential to improve patient outcomes and contribute to the development of a skilled healthcare workforce.